AI TECHNOLOGIES FOR ASSESSING STUDENTS' PRONUNCIATION - Olimova Shakhlobonu Khurshedjonovna (Web of Journals Publishing, 2025)
The advancement of artificial intelligence (AI) has significantly impacted language learning, particularly in the assessment of students' pronunciation. This paper explores various AI-driven technologies used for evaluating pronunciation accuracy, fluency, and intelligibility in second-language learners. It also discusses the advantages and limitations of AI-based pronunciation assessment compared to traditional methods
Keywords: Artificial intelligence, pronunciation assessment, speech recognition, machine learning, deep learning, language learning, phonetic analysis, neural networks.